A study of preinduction transvaginal ultrasonographic cervical length and its comparison with bishop score in predicting successful labour - Kaur, Tajinder; Garg, Shaveta; Kaur, Geetanjali; Kaur, Harsharan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Significant number of induced pregnancies land in caesarean delivery. Cervical assessment is integral to successful outcome of induction of labour. Objective of this study was to study preinduction transvaginal ultrasonographic cervical length and to compare it with Bishop Score in predicting successful labour. Methods: This prospective study was conducted at the department of obstetrics and gynaecology, MMIMSR, Mullana, Ambala on 150 patients. A total of 150 women were studied from January 2015 to June 2016 after taking an informed consent. The sociodemographic particulars were recorded, detailed history was taken and examination performed. Transvaginal ultrasound was done to assess cervical length after evacuation of bladder. Bishop score was then determined by separate observer. The occurrence of vaginal delivery was considered as primary outcome. All statistics collected were entered in statistical software SPSS-15. ROC curves were constructed for both Bishop Score and TVS. Results: The mean gestational age was 38 week 6 days, majority 134 (89.3%) being less than 40 weeks of gestation. The ROC curve for Bishop Score demonstrated better predictability compared to cervical length by TVS. Optimized cut off for Bishop score in addition to TVS was determined by ROC curve to predict successful vaginal delivery, it was ≥ 6 for Bishop score (sensitivity 90.7%, specificity 68.6%, positive predictive value 91.5% and negative predictive value 66.7%) and ≤ 3.0 cm for cervical length on TVS (sensitivity 74.6%, specificity 51.6%, positive predictive value 74.5% and negative predictive value 51.6%). The relation of both cervical length and Bishop score with successful vaginal delivery was found to be statistically significant with p value of 0.0001. Conclusions: The present study indicates that Bishop Score is a better predictor for successful vaginal delivery as compared to cervical length by transvaginal ultrasonography.